2020
DOI: 10.1038/s41398-020-00974-4
|View full text |Cite
|
Sign up to set email alerts
|

The association of PTSD symptom severity with amygdala nuclei volumes in traumatized youths

Abstract: The amygdala is a core component in neurobiological models of stress and stress-related pathologies, including posttraumatic stress disorder (PTSD). While numerous studies have reported increased amygdala activity following traumatic stress exposure and in PTSD, the findings regarding amygdala volume have been mixed. One reason for these mixed findings may be that the amygdala has been considered as a homogenous entity, while it in fact consists of several nuclei with unique cellular and connectivity profiles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…By looking into the relationship of GMV and severity of PTSS, we found negative correlations for the left amygdala and hippocampus in COVID-19 survivors but not in controls. This result was consistent with previous observations of the neurological impairments in the amygdala and hippocampus in patients suffering from PTSS [13,30,31].…”
Section: Discussionsupporting
confidence: 94%
“…By looking into the relationship of GMV and severity of PTSS, we found negative correlations for the left amygdala and hippocampus in COVID-19 survivors but not in controls. This result was consistent with previous observations of the neurological impairments in the amygdala and hippocampus in patients suffering from PTSS [13,30,31].…”
Section: Discussionsupporting
confidence: 94%
“…First, to our knowledge, this is the first evidence for shared genetic aetiology between PTSD and MRI-derived amygdala and putamen volumes. Importantly, imaging studies have previously identified consistent associations between smaller amygdala volumes and PTSD diagnosis 30,31 , in line with the direction of effect in our study; however, such studies necessarily occur after PTSD onset, making causality and direction of effect difficult to infer. Demonstrating shared genetic aetiology between these traits therefore provides novel and vital context to these existing analyses.…”
Section: Discussionsupporting
confidence: 87%
“…In adult military veterans, PTSD is linked with smaller paralaminar and lateral subnuclei, but larger central, medial, and cortical nuclei which are critical to the behavioral and physiological outputs of fear (Morey et al, 2020). In contrast, in youth exposed to a terror attack, PTSD symptoms were associated with smaller volumes across all major subnuclei (Ousdal et al, 2020). These findings suggest that the developmental timing and type of trauma exposure may have important effects on neural phenotypes in PTSD.…”
Section: Introductionmentioning
confidence: 71%